Job Satisfaction’s Dual Role in Transformational Leadership and Turnover Intention: An Islamic Boarding School Business Unit - Prasetyo, Ari; Faizah, Siti Inayatul (Islamic Economics Journal, 2025)
This study examines the dual role of job satisfaction as both a mediating and moderating variable in the relationship between transformational leadership and turnover intention among employees in the business unit of the Sunan Drajat Islamic Boarding School in Lamongan. Adopting an explanatory research design, the study collected data from 93 employees through structured questionnaires and analyzed the results using Structural Equation Modeling (SEM). The findings reveal that job satisfaction significantly mediates the effect of transformational leadership on turnover intention, indicating that transformational leadership can indirectly reduce employees’ desire to leave by enhancing job satisfaction. However, job satisfaction does not significantly moderate this relationship. Conducted within the context of a pesantren, the study suggests that transformational leadership, potentially reflecting Islamic leadership values such as siddiq (truthfulness), fathanah (wisdom), amanah (trustworthiness), and tabligh (communication), can foster job satisfaction and employee retention. Theoretically, this research contributes to the understanding of leadership dynamics in Islamic institutional management, emphasizing the importance of integrating spiritual and ethical dimensions into organizational practices. Practically, this study suggests that Islamic educational institutions should cultivate transformational leadership that embodies Islamic values to enhance employee job satisfaction and ultimately reduce turnover intentions.